A HANDS-ON MANUAL FOR IDENTIFYING AND TREATING HEART FAILURE IN CHILDREN - M. Hadi (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
The incidence of heart failure among children constitutes a major cause of sickness and mortality during their initial years of existence. Whereas well-established guidelines are present for managing heart failure in adults, a corresponding consensus for the pediatric group is lacking. Within a healthcare setting, it's of paramount importance to establish a correct diagnosis and identify the root cause for the most effective intervention. Primary interventions include diuretics and angiotensin-converting enzyme inhibitors, however, the utilization of beta-blockers and cardiac therapy devices is less common in pediatric cases as compared to adults. For severe conditions, heart transplant remains the go-to therapeutic choice. Additionally, left ventricular assist devices can be employed as a temporary solution awaiting transplantation (due to scarcity of organ donors), recovery (in instances of myocarditis), or a definitive solution (for patients with systemic disease).